Usia Kawin Perempuan dalam Paradigma Hukum Islam - Nur Anissa; Arfin Hamid; Ratnawati Ratnawati (Universitas Medan Area, 2021)
Islamic law does not determine the age of marriage for women, but only provides the conditions according to the Surah An-Nur Verse (6) and (32), Marriage may be carried out if it is old enough or fit for marriage or maturity